A Comparative Analysis of Quality Metrics between Different Image Enhancement Techniques for Facial Sketches - B Achar, Swathi; M S, Sannidhan; Bhandary, Abhir (International Journal of Engineering and Technology, 2018)
Enhancement of an image is considered as one of the important aspect in image processing. It is also considered to be major pre-processing step which is used in vision systems and lot many image processing applications. It is used in law enforcement application such as in crime investigation process, identification and apprehension of criminals by matching facial sketches to the mug-shot photos. Here skilled forensic artists are used to draw sketches based on the vocal description provided by the victim or eye witness. The sketches drawn might be blurred, less quality images. So to measure the quality of sketches, here three quality assessment methods are used in this study such as PSNR (Peak Signal-to-Noise Ratio), MSE (Mean Squared Error) and the SSIM (Structural Similarity index). Hence this paper aims in discovering a better image enhancement technique for the sketches from different databases by comparative analysis of aforesaid quality metrics along with their time complexity factor. The method has considered both viewed sketches and composite sketches as a source of input.